Perianal Condyloma Acuminata: Factors that Contribute to the Recurrence - Jeo, Wifanto S.; Sugiharto, Bobby; Kekalih, Aria (The New Ropanasuri Journal of Surgery, 2018)
Introduction. Condyloma Acuminata (CA) is the most common sexually transmitted disease caused by HPV with high recurrence rate up to 70%. Factors contribute to the recurrence such as age, site of predilection, previous treatment, HIV infection and sexual behavior were noted in perianal CA. To date the correlation of these factors to the recurrence remains unknown. Method. A cross sectional study was conducted. Patients with history of CA managed in clinic of surgery during period of January 2010 to June 2015 were reviewed. Subject characteristics, i.e. age, infected site, previous treatment, HIV infection and sexual behavior and recurrence were the variables of the study. Data collected from medical record were statistically analyzed. Significant correlation found if p value <0.05. Results. There were 48 subjects with the history of CA. On the analysis, age variable has a significant correlation with the recurrence p = 0.008 (OR = 5.83; 95% CI 1.66–20.56;). The recurrence was higher in productive age compared to non–productive age. Previous anal CA and high risk negative sexual behavior showed a higher recurrence risk than previous non–anal CA and positive sexual behavior (OR = 1.89 and 2.14, respectively). Conclusion. There was significant correlation between age and CA recurrence, anal CA and negative sexual behavior showing 1.89 and 2.14 times, respectively more likely to have recurrence (New Ropanasuri J Surg.2018;3(2):e218).